(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Secondary Infertility is defined as the inability to conceive following at least one prior conception. Ovulatory dysfunction contributes 30-40% of infertility. Polycystic ovarian syndrome is a common endocrinopathy typified by oligo/anovulation, signs of androgen excess, and multiple ovarian cysts. In Ayurveda, Vandhyatha (infertility) is considered as a complication of Yoni vyapath and is also considered as Artavavaha srotodushti lakshana. This is a case report of 30 years old lady complaining of inability to conceive a second child, heavy menstrual bleeding and curdy white discharge per vagina associated with itching. On USG, she was diagnosed with Polycystic Ovarian Syndrome. She also had severe allergic complaints and skin rashes. In this case treatment was given primarily to correct the Rakta dushti which was causing Artava dushti in the form of excessive bleeding. For that, initially in the bleeding phase, medicines for Rakta sthambana were given and after the stoppage of bleeding, medicines were given for correction of Rakta dushti. After achieving the menstrual regulation, the patient was given medicines for Vata kapha dushti for treating her Upaplutha condition. For the management of Yoni roga, she was given Sthanika karmas (local treatment) Yoni dhawana and Yoni pichu. Also local application of Nalpamaradi keram was done to reduce her vulval itching. The outcome of the treatment resulted in conception and delivered a full term female baby. So the present case signifies the effect of Ayurvedic management in the field of infertility.